Endovascular treatment for ruptured abdominal aortic aneurysm - Badger, Stephen (Cochrane Database Syst Rev, 2017)
BACKGROUND: An abdominal aortic aneurysm (AAA) (pathological enlargement of the aorta) is a condition that can occur as a person ages. It is most commonly seen in men older than 65 years of age. Progressive aneurysm enlargement can lead to rupture and massive internal bleeding, which is fatal unless timely repair can be achieved. Despite improvements in perioperative care, mortality remains high (approximately 50%) after conventional open surgical repair. Endovascular aneurysm repair (EVAR), a minimally invasive technique, has been shown to reduce early morbidity and mortality as compared to conventional open surgery for planned AAA repair. More recently emergency endovascular aneurysm repair (eEVAR) has been used successfully to treat ruptured abdominal aortic aneurysm (RAAA), proving that it is feasible in select patients; however, it is unclear if eEVAR will lead to significant improvements in outcomes for these patients or if indeed it can replace conventional open repair as the preferred treatment for this lethal condition. This is an update of the review first published in 2006. OBJECTIVES: To assess the advantages and disadvantages of emergency endovascular aneurysm repair (eEVAR) in comparison with conventional open surgical repair for the treatment of ruptured abdominal aortic aneurysm (RAAA). This will be determined by comparing the effects of eEVAR and conventional open surgical repair on short‐term mortality, major complication rates, aneurysm exclusion (specifically endoleaks in the eEVAR treatment group), and late complications. SEARCH METHODS: For this update the Cochrane Vascular Information Specialist searched the Cochrane Vascular Specialised Register (last searched June 2016), CENTRAL (2016, Issue 5), and trials registries. We also checked reference lists of relevant publications. SELECTION CRITERIA: Randomised controlled trials in which participants with a clinically or radiologically diagnosed RAAA were randomly allocated to eEVAR or conventional open surgical repair. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed studies identified for potential inclusion for eligibility. Two review authors also independently completed data extraction and quality assessment. Disagreements were resolved through discussion. We performed meta‐analysis using fixed‐effect models with odds ratios (ORs) and 95% confidence intervals (CIs) for dichotomous data and mean differences with 95% CIs for continuous data. MAIN RESULTS: We included four randomised controlled trials in this review. A total of 868 participants with a clinical or radiological diagnosis of RAAA were randomised to receive either eEVAR or open surgical repair. Overall risk of bias was low, but we considered one study that performed randomisation in blocks by week and performed no allocation concealment and no blinding to be at high risk of selection bias. Another study did not adequately report random sequence generation, putting it at risk of selection bias, and two studies were underpowered. There was no clear evidence to support a difference between the two interventions for 30‐day (or in‐hospital) mortality (OR 0.88, 95% CI 0.66 to 1.16; moderate‐quality evidence). There were a total of 44 endoleak events in 128 participants from three studies (low‐quality evidence). Thirty‐day complication outcomes (myocardial infarction, stroke, composite cardiac complications, renal complications, severe bowel ischaemia, spinal cord ischaemia, reoperation, amputation, and respiratory failure) were reported in between one and three studies, therefore we were unable to draw a robust conclusion. We downgraded the quality of the evidence for myocardial infarction, renal complications, and respiratory failure due to imprecision, inconsistency, and risk of bias. Odds ratios for complications outcomes were OR 2.38 (95% CI 0.34 to 16.53; 139 participants; 2 studies; low‐quality evidence) for myocardial infarction; OR 1.07 (95% CI 0.21 to 5.42; 255 participants; 3 studies; low‐quality evidence) for renal complications; and OR 3.62 (95% CI 0.14 to 95.78; 32 participants; 1 study; low‐quality evidence) for respiratory failure. There was low‐quality evidence of a reduction in bowel ischaemia in the eEVAR treatment group, but very few events were reported (OR 0.37, 95% CI 0.14 to 0.94), and we downgraded the evidence due to imprecision and risk of bias. Six‐month and one‐year outcomes were evaluated in three studies, but only results from a single study could be used for each outcome, which showed no clear evidence of a difference between the interventions. We rated six‐month mortality evidence as of moderate quality due to imprecision (OR 0.89, 95% CI 0.40 to 1.98; 116 participants). AUTHORS' CONCLUSIONS: The conclusions of this review are currently limited by the paucity of data. We found from the data available moderate‐quality evidence suggesting there is no difference in 30‐day mortality between eEVAR and open repair. Not enough information was provided for complications for us to make a well‐informed conclusion, although it is possible that eEVAR is associated with a reduction in bowel ischaemia. Long‐term data were lacking for both survival and late complications. More high‐quality randomised controlled trials comparing eEVAR and open repair for the treatment of RAAA are needed to better understand if one method is superior to the other, or if there is no difference between the methods on relevant outcomes.